Partisipasi Masyarakat Lokal dalam Pengembangan Kawasan Wisata Geopark Batur di Kintamani Kabupaten Bangli - Wiramatika, I Gede; Sunarta, I Nyoman; Anom, I Putu (Jurnal Master Pariwisata (JUMPA), 2021)
This study aims to examine the participation of local communities in the development of the Batur Geopark tourist area in Kintamani, Bangli Regency regarding the participation of local communities in the development of the Batur Geopark tourist area, the obstacles faced by local communities in the development of the Batur Geopark tourist area, and the efforts made by the Government in developing the tourist area Batur Geopark. In this study the data collected through interviews, observations, literature studies, documentation studies, and the Community then analyzed the data using qualitative descriptive data analysis techniques. The presentation of data analysis in this study was carried out qualitatively through verbal delivery with interpretative descriptive techniques. The results of this study indicate that in the development of the Batur Geopark tourist area there are still several obstacles faced in its development. The government's efforts in developing the Batur Geopark tourist area are: the formation of a tourism awareness group, tightening permits for facility construction, establishing a management agency, procuring tourism facilities, improving the road infrastructure, structuring material excavation at the foot of Mount Batur, holding promotions, and providing tourism training. The forms of community participation in the development of the Batur Geopark tourist area are: preserving the biodiversity of flora and fauna, building tourism facilities, developing the typical Kintamani major culinary, cultural preservation, taking jobs in the tourism sector, nature conservation, and the formation of security officers. Keywords: Community Participation, Tourism Development, Geopark